2015
DOI: 10.1038/ncb3216
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association between YAP/TAZ/TEAD and AP-1 at enhancers drives oncogenic growth

Abstract: YAP/TAZ are nuclear effectors of the Hippo pathway regulating organ growth and tumorigenesis. Yet, their function as transcriptional regulators remains underinvestigated. By ChIP-seq analyses in breast cancer cells, we discovered that the YAP/TAZ transcriptional response is pervasively mediated by a dual element: TEAD factors, through which YAP/TAZ bind to DNA, co-occupying chromatin with activator protein-1 (AP-1, dimer of JUN and FOS proteins) at composite cis-regulatory elements harbouring both TEAD and AP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

115
1,101
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 965 publications
(1,222 citation statements)
references
References 58 publications
(96 reference statements)
115
1,101
4
2
Order By: Relevance
“…4B). In addition, it has been reported that several genes are regulated by YAP, including connective tissue growth factor (CTGF) and Cyr6128, 29, 30, 31. We next examined the mRNA levels of the two genes by real‐time quantitative RT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…4B). In addition, it has been reported that several genes are regulated by YAP, including connective tissue growth factor (CTGF) and Cyr6128, 29, 30, 31. We next examined the mRNA levels of the two genes by real‐time quantitative RT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…It would be worthwhile to further delineate the Hippo signaling cascade and the cross-talk between the flow-sensitive pathways that modulate YAP/TAZ activities. YAP/TAZTEADs complex has been shown to induce expressions of its target genes controlling cell growth and cell cycle progression (9,27). It is likely that the OS-activated YAP/TAZ act through TEADs to promote EC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that FGFR1, -2, and -4 are direct transcriptional targets of YAP. Although the cognate YAP transcription factors are TEADs (34,35), in CCA cells YAP partners with TBX5 to promote up-regulation of FGFR1, -2, and -4. Prior studies have demonstrated an essential role for ␤-catenin-YAP-TBX5 in tumors with activated WNT signaling (6).…”
Section: Discussionmentioning
confidence: 99%